Health risk assessment and microplastic pollution in streams through accumulation and interaction by heavy metals - A.M. Sabilillah; F.R. Palupi; B.K. Adji; A.P. Nugroho (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The threat posed by microplastics to humans through fish consumption is potentially great due to microplastics’ capacity to adsorb heavy metals. The Code and Gajahwong streams have suffered from plastic and heavy metal pollution as the major rivers in Yogyakarta, Indonesia. However, little is known about the cumulative danger caused by the association of the microplastic and heavy metals. A thorough analysis of the extent of the health risks that people who consume fish from these rivers may experience is urgently needed. Hence, this study aimed to study microplastic pollution accumulated by fish in Code and Gajahwong streams, analyze the interactions with heavy metals, and assess the potential health risks.METHODS: Fish sample collection was conducted in three stations by considering the severity of plastic pollution. Microplastics were extracted from the gills, digestive tract, muscle, and water and then characterized based on the number, size, shape, color, and type of polymer. Potential health risks were evaluated based on the potential ecological risk index, polymer hazard index, pollution load index, estimated daily intake, target hazard quotient, total target hazard quotient, and target cancer risk.FINDINGS: Microplastics have contaminated the streams and fish and were dominated by small-sized green fibers and low-density polyethylene polymer. The pollution was related to human activities around the streams. The highest accumulation in fish was found in the digestive organs. Lead and cadmium have been associated with microplastics. The calculation of the potential ecological risk index and polymer hazard index showed that the medium risk of microplastic contamination in both streams. Based on the values of estimated daily intake, target hazard quotient, total target hazard quotient, and target cancer risk, short-term consumption of fish from the streams carries a low risk, but it will increase over time and pose a serious harm in the long term.CONCLUSION: Given that most of the microplastics found were associated with lead and cadmium, they can increase the risk to human health due to the transfer of microplastics through food chains. Mitigation efforts involving various stakeholders, community involvement, and continuous education must be continuously pursued. This study significantly contributes to the current problem of environmental pollution by means of microplastic threats associated with heavy metals and provides a thorough health risk assessment applicable to other rivers and mitigation efforts that must be exerted to achieve sustainability.